Kapasitas Fungsional Dan Kualitas Hidup Lansia Wanita Dengan Osteoartritis Lutut - Adawiyah, Asyifa Robiatul; Suratmi, Tri; W. Rahardjo, Tri Budi (LPPM Universitas Respati Indonesia, 2020)
Elderly women with knee osteoarthritis have higher symptoms, more pain, and more functional loss related to quality of life (27.5%) than elderly men (21.8%). The purpose of this study to examine the association of functional capacity and quality of life of elderly women with knee osteoarthritis. Type of analytic survey research using cross sectional design. The population in this study were all elderly women osteoarthritis (age> 45 years) in Bekasi City General Hospital as many as 80 elderly women by total population. Data was collected by the primary data through interviews using a questionnaire. Data analysis with univariate and bivariate. The average score obtained is 42.93% for quality of life, which means they have a poor quality of life. The results of bivariate analysis showed that the correlation between the Osteoarthritis Index and quality of life was r = -0.601 (p value <0.05) and the correlation between Functional Capacity (Activity od Daily Living; Instrument Activity of Daily Living; and Social Mental Activity) with Quality of Life -as equal to r = 0.649; 0.792; 0.607 (p value <0.05). In conclusion, there is a significant relationship between the Osteoarthritis Index and functional capacity with quality of life in elderly women with knee osteoarthritis at the Bekasi City General Hospital in 2016. Keywords: Osteoarthritis, Functional Capacity, Quality of Life, Elderly Health